The poem “Bunga Ilmu Itu” by Dinullah Rayes:Riffaterre's Semiotic Studies - Diana, Jumianti; Patihah, Marwah Ernia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to reveal the meaning of the poetry and text which became the background for the creation of the poem "The Flower of That Science" by Dinullah Rayes. The research method used is a descriptive qualitative method. Data was collected using library techniques, listen and take notes. Data analysis was carried out using the Riffaterre semiotic model reading method. The research results show that the meaning of knowledge or intelligence possessed by humans is a gift from God. Humans should not be arrogant. It is better if the intelligence you have can be felt by many people. So that intelligence will be beautiful because of its benefits. Apart from having meaning, the poem has an intertextual relationship with Al-Baqarah verses: 31-34.  So Al-Baqarah verses: 31-34 become a hypogram from the second line to the fourteenth line of the poem. This serves to remind us that the knowledge or intelligence possessed by humans is a gift from God. The fifteenth to twenty-fifth lines of the poem show the poet's knowledge of the character he is familiarly calling Zul as someone who has intelligence and provides benefits to many people.